Morphological features of a pancreas of children who have died aged till 6 months from a HIV-infected of mothers. - Sorokina, I. V.; Sherstiuk, S. A. (Морфологія / Morphologia / Morfologìâ, 2011)
In a pancreas of children who have died aged till 6 months from a HIV-infected of mothers thanks to morphological and morphometric to researches it is taped failure of compensatory possibilities of an organ shown by stroma growth, inhibition of functional activity of the exocrine apparatus, in a kind of reduction of diameter of an acinus, hypotrophy of exocrine cells and augmentations of a nuclei-cytoplasm index, and also population reduction в - cells against reduction of their functional activity.